The Consequences of Colonialism to the History and Lives of the Garifuna People of St. Vincent. - Maria Fernanda de Almeida (Caribbean Quilt, 2023)
Garifuna people have lived on the Caribbean island of St. Vincent for over 300 years. Enslaved Africans who had survived the sinking of two Spanish ships in the 1600s became the first non-American group to settle on the island. Land ownership struggles, racism and discrimination and attempts at cultural erasure mark their history. This paper analyzes the relations and consequences of colonialism to the current status of the neglect of the Garifuna of St. Vincent. It argues that the arrival of Spanish, French, and British to St. Vincent influenced the genocide of Caribs, the creation of stereotypes associated with their people, and the spread of academic literature based on false narratives of their stories. These consequences led to the current struggles that the Garifuna face on the island and in their fight to rewrite historical memory and knowledge. Finally, it is essential to recognize their progress in rebuilding an identity of self-recognition by restoring historical memory and demanding governmental recognition. They have sought to situate themselves as people who live, fight, and exude their mixed culture of Arawak and black ancestry in a transnational territory. However, their case is complex. They carry indigenous and African identities, which insert them into movements and struggles on transnational networks and narratives of belonging around indigenous and black or Afro descendants' movements.